Randomized, open-label, phase III study comparing patupilone (EPO906) with pegylated liposomal doxorubicin in platinum-refractory or -resistant patients with recurrent epithelial ovarian, primary fallopian tube, or primary peritoneal cancer - Colombo, N.; Kutarska, E.; Dimopoulos, M.; Bae, D.-S.; Rzepka-Gorska, I.; Bidzinski, M.; Scambia, G.; Engelholm, S.A.; Joly, F.; Weber, D.; El-Hashimy, M.; Li, J.; et al. (Journal of Clinical Oncology, 2012)
Purpose: This study compared the efficacy and safety of patupilone with those of pegylated liposomal doxorubicin (PLD) in patients with platinum-refractory or -resistant epithelial ovarian, primary fallopian tube, or primary peritoneal cancer. Patients and Methods: Patients with three or fewer prior regimens were eligible if they had received first-line taxane/ platinum-based combination chemotherapy and were platinum refractory or resistant. Patients were randomly assigned to receive patupilone (10 mg/m 2 intravenously every 3 weeks) or PLD (50 mg/m2 intravenously every 4 weeks). Results: A total of 829 patients were randomly assigned (patupilone, n = 412; PLD, n = 417). There was no statistically significant difference in overall survival (OS), the primary end point, between the patupilone and PLD arms (P = .195; hazard ratio, 0.93; 95% CI, 0.79 to 1.09), with median OS rates of 13.2 and 12.7 months, respectively. Median progression-free survival was 3.7 months for both arms. The overall response rate (all partial responses) was higher in the patupilone arm than in the PLD arm (15.5% v 7.9%; odds ratio, 2.11; 95% CI, 1.36 to 3.29), although disease control rates were similar (59.5% v 56.3%, respectively). Frequently observed adverse events (AEs) of any grade included diarrhea (85.3%) and peripheral neuropathy (39.3%) in the patupilone arm and mucositis/stomatitis (43%) and hand-foot syndrome (41.8%) in the PLD arm. Conclusion: Patupilone did not demonstrate significant improvement in OS compared with the active control, PLD. No new or unexpected serious AEs were identified. © 2012 by American Society of Clinical Oncology.